Lego–lego and informal politics—an exploration of cultural democracy in Bugis society, Indonesia - Prianto, Andi Luhur; Subair, Nurlina; Wardana, Data; Amri, Aqmal Reza (Frontiers in Political Science, 2025)
This study examines how the Bugis concept of lego-lego, the veranda at the front of a traditional stilt house, serves as an indigenous public sphere that sustains everyday life democratic life. It seeks to reinterpret the idea of cultural democracy through the ethical values and spatial traditions that shape Bugis society. Drawing on a qualitative ethnographic approach, the research combines participant observation, semi-structured interviews with customary leaders and community members, and the analysis of local documents. The findings show that lego-lego provides a participatory setting where people come together to talk, listen, and reach shared understanding through practices such as tudang sipulung. These interactions are guided by Bugis moral principles; siri’, pesse’, sipakatau, and sipakalebbi, which nurture dignity, empathy, humanize, and respect to each other. The study argues that lego-lego embodies cultural democracy by linking informal acts of deliberation to collective decision-making beyond formal institutions. In doing so, it offers an indigenous perspective on democracy and broadens current discussions of deliberative and informal politics in Southeast Asia